Engaging talk: one teacher's scaffolding of collaborative talk. (4th March 2017) - Newman, Ruth M. C.
ABSTRACT: This paper reports on an ESRC and British Telecom funded study which explored the teaching of collaborative talk in the secondary English classroom. While research signals the crucial role of the teacher in promoting dialogic pedagogies, less specific attention has been given to how teacher discourse can shape the development of students' collaborative dialogue. Through multiple data sources, this paper will explore the discourse of one of two project teachers who implemented an intervention which, drawing on research in educational linguistics, emphasised the role of metatalk in developing students' collaborative talk. In particular, it will examine how one teacher facilitated and modelled productive interaction, scaffolding students' understanding and appropriation of the expectations and language of collaborative talk. This paper will argue that teachers must utilise and model the talk they promote, and will consider the communicative and interpersonal aspects of this scaffolding process. It will also contribute to the argument that the teacher's role is central in the promotion and development of productive peer dialogue as a component of a repertoire of classroom talk.